Internal Validity and Internal Validity Threats - Imas Siti Masuroh; Inda Dzil Mustaqim (al-Afkar, Journal For Islamic Studies, 2026)
A study is said to be valid if it has a proven causal relationship between its variables. A study is said to have validity if it can minimize various confounding factors that can affect the results and the level of trust in the study. Several threats to internal validity that can affect the results of the study The purpose of this study is to describe the role of internal validity in a scientific study and the threats to internal validity. The articles used as sources of literature review in this study are based on Google Scholar and PubMed data. The search for research literature uses the keywords "internal validity" and "threats to internal validity". The analysis technique used is the narrative method by grouping the data that was excavated. This study aims to describe internal validity and threats to internal validity in research. Threats to internal validity history, maturation, subject characteristics, mortality, location, subject attitude, instrumentation, testing, regression, implementation. Threat control techniques random assignment, blocking, matching, placebo, in addition to standardization of conditions, research subject information, detailed research information, and selection of appropriate designs internal validity ensures that research has a high level of trust and accuracy. Researchers must be confident that threats have been successfully controlled and their risks minimized so that they do not affect the research. Various techniques can be used to control threats to internal validity. Threats cannot be completely eliminated but can be anticipated and controlled.